2013
DOI: 10.1177/1060028013511229
|View full text |Cite
|
Sign up to set email alerts
|

Time to Positivity of Blood Cultures Supports Antibiotic De-escalation at 48 Hours

Abstract: Few true BSIs are detected after more than 48 hours of culture incubation. Clinicians may adjust empirical antibiotic coverage at this time with little risk for subsequent bacterial pathogen detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
38
1
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 25 publications
6
38
1
3
Order By: Relevance
“…For example, consensus recommendations on perioperative prophylaxis recommend limiting antibiotics to a single dose or 24 hours for most surgeries (48 hours in the setting of sternotomy) (19). Blood cultures, as another example, now have a median time to positivity of 13.7 hours and a negative predictive value of 99.8 at 48 hours, and may be appropriate for rapid molecular screening for resistance mutations, thus permitting faster antimicrobial deescalation than was feasible in an earlier era of clinical microbiology (20). Limiting antibiotic duration may be complicated by senior leadership who may have trained in an era when 10−14 or 10−21 days regimens were routine (21), and who have not adapted to newer evidence (22).…”
Section: Antibiotic Stewardshipmentioning
confidence: 98%
“…For example, consensus recommendations on perioperative prophylaxis recommend limiting antibiotics to a single dose or 24 hours for most surgeries (48 hours in the setting of sternotomy) (19). Blood cultures, as another example, now have a median time to positivity of 13.7 hours and a negative predictive value of 99.8 at 48 hours, and may be appropriate for rapid molecular screening for resistance mutations, thus permitting faster antimicrobial deescalation than was feasible in an earlier era of clinical microbiology (20). Limiting antibiotic duration may be complicated by senior leadership who may have trained in an era when 10−14 or 10−21 days regimens were routine (21), and who have not adapted to newer evidence (22).…”
Section: Antibiotic Stewardshipmentioning
confidence: 98%
“…In the largest cohort study to date by Martinez TTP found in the current study was relatively longer than in previous studies. 11,12 This can be explained by the difference in the definition of TTP. In our study, TTP was measured starting from the time of BC collection at the bedside.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…At present, the majority of BCs becomes positive within 24 hours. [11][12][13] In previous studies, data on patients with neutropenia are limited.…”
mentioning
confidence: 99%
“…It usually takes 1 to 3 days to obtain both the identification and the antimicrobial susceptibility profile of the pathogen. The major limitation of blood culture methods is that they require a median timeto-positivity of 12 to 17 hours [4]. Another limitation of this method is that the presence of unculturable or fastidious microorganisms may decrease its sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, this technology is able to detect the resistance to some antibiotics [9], such as the presence of -lactamases (including carbapenemases), methicillin-resistant Staphylococcus aureus, and even vancomycin-resistant Enterococcus spp. However, this technology relies on culture and, therefore, a median of 12-to 17-hour delay is unavoidable [4]. In order to further accelerate the diagnostic process, it is desirable to detect and identity pathogens directly from the patient's blood, avoiding the culture step.…”
Section: Introductionmentioning
confidence: 99%